Influence of nitrate - ammonium ratio on the growth, nutrition, and metabolism of sugarcane - Boschiero, Beatriz Nastaro (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.